2013
DOI: 10.1182/blood-2013-06-506873
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of FLI1 and RUNX1 mutations in families with excessive bleeding and platelet dense granule secretion defects

Abstract: Key Points• Novel FLI1 and RUNX1alterations were identified in 6 of 13 patients with excessive bleeding and platelet granule secretion defects.• Two FLI1 alterations predicting amino acid substitutions in the DNAbinding domain of FLI1 abolished transcriptional activity of FLI1.We analyzed candidate platelet function disorder genes in 13 index cases with a history of excessive bleeding in association with a significant reduction in dense granule secretion and impaired aggregation to a panel of platelet agonists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
107
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 17 publications
11
107
0
Order By: Relevance
“…Seven variants have previously been published as part of two separate publications from the UK-GAPP study group. 8,15 Classification of the 28 variants occurring within the known IT-related genes, following the interpretation guidelines set out by Richards et al, 17 revealed four variants to be "pathogenic", 13 to be "likely pathogenic" and 11 to be of "uncertain significance". Variants classified as "pathogenic" were either already known to be a genetic cause of IT; ANKRD26; c.-126T>G in F2.I and MYH9; p.Arg1165Cys in F9.I, or were predicted to be loss-of-function variants in genes for which a loss of function is known to cause disease; FLI1; p.Asn331Thr fs*4, in F4.I and F4.II and RUNX1; pTrp79* in P12.I.…”
Section: Variants In Known Thrombocytopenia-causing Genesmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven variants have previously been published as part of two separate publications from the UK-GAPP study group. 8,15 Classification of the 28 variants occurring within the known IT-related genes, following the interpretation guidelines set out by Richards et al, 17 revealed four variants to be "pathogenic", 13 to be "likely pathogenic" and 11 to be of "uncertain significance". Variants classified as "pathogenic" were either already known to be a genetic cause of IT; ANKRD26; c.-126T>G in F2.I and MYH9; p.Arg1165Cys in F9.I, or were predicted to be loss-of-function variants in genes for which a loss of function is known to cause disease; FLI1; p.Asn331Thr fs*4, in F4.I and F4.II and RUNX1; pTrp79* in P12.I.…”
Section: Variants In Known Thrombocytopenia-causing Genesmentioning
confidence: 99%
“…An in-house flowcytometry assay was developed to assess platelet function in patients with platelet counts in platelet-rich plasma <1x10 8 /mL (n=22). Platelets from individuals with borderline platelet counts in platelet-rich plasma, between 1.0 and 1.5x10 8 /mL, were assessed using both assays (n=16).…”
Section: Platelet Preparation and Platelet Function Testingmentioning
confidence: 99%
See 3 more Smart Citations